99.6k views
5 votes
Josh examines the expression5^-m/5^m where m is greater than 0.He claims that the expression has a value equal to 1 because it sim-plifies to 5^0, and any integer to the 0 power is 1.Is Josh correct? Explain why or why not.Answer in complete sentences.

1 Answer

3 votes

we have the expression


(5^((-m)))/(5^m)=5^((-m-m))=5^((-2m))=(1)/(5^((2m)))=(1)/(25^m)

therefore

Josh is not correct

because the expression is not equal to 1

when subtracting, the exponent is -2m, not zero

User Strelok
by
4.6k points